Econometric models and methods - Christ, Carl F. (New York: John Wiley & Sons, 1966)
The aim of this book is not to cover it all, but rather to give the persevering reader a feeling for what econometrics is like and a technical understanding of some of its important models and methods. The book is divided into three parts. Part One (Chapters I-II) is a simple introduction, designed to illustrate most of the main issues in the book in a not very technical manner. Part Two (Chapters III-VI) discusses theoretical econometric models. Part Three (Chapters VII-XI) deals with empirical methods in econometrics, especially with the identification of econometric parameters, statistical estimation and statistical testing.
Incudes bibliographical references: p. 673-688 and index.
rpm 28/03/2018
Loans
Keywords: Econometrics